Про конспецифічність Thyrostroma tiliae та Stegonsporium compactum var. tiliae - Якунькін, Яків Дмитрович; Згонник, Микола Олексійович (Київ : Інститут ботаніки ім. М.Г. Холодного НАН України, 2021)
Thyrostroma tiliae Senwanna, Wanas., Bulgakov, Phookamsak & K.D. Hyde (2019) was described recently as a new species for science. After in detail comparison with the holotype of Stegonsporium compactum var. tiliae Sacc. in Potebnia (1907), we can assume that it is the same species. The name Thyrostroma tiliae needs to be formed as a new combination based on the mentioned above variety
On the conspecificity of Thyrostroma tiliae and Stegonsporium compactum var. tiliae
Keywords: fungi; biodiversity; herbarium; collection; type; revision; Ukraine